2020
DOI: 10.1177/1010539520975266
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Effects of a Community-Based Self-Management Intervention for Patients With Type 2 Diabetes in China: Outcomes at 2-Year Follow-up of a Randomized Trial

Abstract: This research is to evaluate the lasting effects of a community-based self-management intervention for patients with type 2 diabetes at 2-year follow-up in China. Five hundred patients with diabetes were recruited and randomly divided into intervention group and control group. Eight times standardized self-management intervention group activities were conducted. The results of physical examination, biochemical laboratory examination, health behavior, and self-efficacy information were collected before interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Diabetic patients benefit from communitybased health follow-up management to better regulate their blood glucose levels. The effects of the intervention are long-term (30,31). Health follow-up management can also help hemodialysis patients produces increases in their blood phosphorus levels, improvements in their physical and mental health, and improvements in their quality of life (32).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients benefit from communitybased health follow-up management to better regulate their blood glucose levels. The effects of the intervention are long-term (30,31). Health follow-up management can also help hemodialysis patients produces increases in their blood phosphorus levels, improvements in their physical and mental health, and improvements in their quality of life (32).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Spencer et al ( 19 ) on effectiveness of community health worker led diabetes self-management education demonstrated achieving and maintaining improvements in the key outcomes. Another study conducted by Jiang et al ( 20 ) found that community- based self-management group intervention for patients with diabetes has long term effects.…”
Section: Discussionmentioning
confidence: 99%
“…14 Blood glucose testing by glucose meter is useful for public health management of DM in the community. 17-19 For success in lifestyle intervention, glucose results obtained from glucose meter and operated at HPHs should be accurate. The storage condition of test strip was an influent factor for the accuracy and precision of blood glucose testing by glucose meter, therefore staff at HPHs must consider inappropriate temperatures and RH for test strip storage.…”
Section: Discussionmentioning
confidence: 99%